Self-perception of body image in the physical education course students - Rech, Cassiano Ricardo; Araújo, Eliane Denise da Silveira; Vanat, Joyce Do Rocio (Brazilian journal of physical education and sport, 2010)
This study aimed at evaluating the self-perception of the body image (BI) and associating the BI to socio-demographic indicators, nutritional state and level of physical activities in university students. A cross-sectional study with 394 students was made (136 men and 158 women). The BI perception was measured by means of the silhouette scale, indicating the present silhouette (PS), the ideal silhouette (IS), and the ideal silhouette of the opposed gender (ISO). Demographic variables were also collected (gender, age, part of the day in which they study, occupation), socio-economical level, nutritional state (body mass index) and the level of physical activity (IPAQ - Short version). The descriptive analysis and the qui-square association test were used to analyze the data. The dissatisfaction prevalence with the BI was of 61.2% (n = 180), being 61% men and 61.4% women. The silhouette 2 was pointed by 57% and 38.2% of women and men as the IS, respectively. Silhouettes 3 and 4 were pointed as the IS by 38.2% of the women and 39.7% of the men. Silhouette 3 was identified as the ISO (63.2% male and 56.3% female). Women showed a higher prevalence (67.6%) of having a smaller silhouette than the present one. Men showed a tendency (66.7%) to prefer a bigger silhouette than the present one. Besides the gender, the BI perception was associated with the nutritional state (p < 0.05), in which it was observed that 78.7% of the overweight subjects to have a smaller silhouette than they have at present. The conclusion is that the BI self-perception was associated with gender and nutritional state of the university students